(untitled) (Research, Society and Development, 2020)
The study aimed to evaluate the prevalence of mental disorders and the associated factors in Physical Education Teachers (PET) from the public school system in a municipality on the western border of Rio Grande do Sul. The study sample consisted of 46 PET. To assess mental health and identify mental disorders, the Brazilian version of the Mini International Neuropsychiatric Interview was used and to check the levels of Physical Activity, the short version of the International Physical Activity Questionnaire was used. To identify the characteristics and conditions of the work, a questionnaire designed specifically for the study was used. The results found in the present study indicated an important prevalence of CMDs (34.8%) in PET in the public network of a municipality, in the interior of RS, Brazil. Additionally, we identified that the majority of teachers with disorders are female (75%), comprise the age group of 40 to 60 years (56.7%) and perceive their salary as bad (56.2%). Through the study it was possible to identify a relatively young population of teachers, more than half of them female, with low remuneration and with demand for mental health. Still, work aspects, such as noise at school, physical structure and the relationship with colleagues were factors that were associated with the presence of mental disorders in the evaluated teachers.